Conflict Management in Public Organizations: A Human Resource Management Perspective - Yulianah, Yulianah (International Journal of Demos (IJD), 2025)
Abstract Conflict is an inevitable phenomenon within organizations, including public organizations that have complex bureaucratic structures and involve various interests. This study aims to analyze the forms of conflict that occur in public organizations, evaluate the role of Human Resource Management in handling conflicts, and identify effective conflict management strategies from a Human Resource Management perspective. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and document study. The results show that conflict management in public organizations is highly influenced by the effectiveness of the role of Human Resource Management. Through strategic approaches such as communication training, implementation of clear conflict resolution policies, and the strengthening of a collaborative organizational culture, Human Resource Management is able to minimize potential conflicts as well as resolve existing conflicts constructively. This study also finds that the most common forms of conflict are vertical conflict and role conflict, mainly due to mismatched perceptions, disproportionate workloads, and ineffective communication. Therefore, optimizing the role of Human Resource Management not only impacts conflict resolution but also enhances organizational performance and the quality of public services as a whole. Keywords: Conflict Management, Public Organization, Human Resource Management, Conflict Resolution Strategy.